2017
DOI: 10.1177/1077559517725402
|View full text |Cite
|
Sign up to set email alerts
|

Engagement and Adherence With ezPARENT, an mHealth Parent-Training Program Promoting Child Well-Being

Abstract: Mobile health (mHealth) interventions use mobile technology (tablets and smartphones) delivery platforms for interventions to improve health outcomes. Despite growing acceptance, there is little understanding of how consumers engage with and adhere to mHealth interventions. This study analyzes usage data from the intervention arm ( n = 42) of a randomized clinical trial testing the efficacy of the ezPARENT program and provides recommendations for using engagement and adherence metrics. Engagement was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…These types of interventions were usually adapted from existing EBIs (71%). eHealth strategies applied include web-based parenting modules (included 4 to 12 interactive or structured parenting sessions), with (44, 45, 5253, 54, 56, 57) or without (42, 47, 48, 50, 55) additional e-communication or e-support for parents (e.g., phone coaching, e-reminders, feedback messaging, email, social media groups). There were also some studies focused on parent support interventions (including information and emotion support) and wellness promotion (purpose) for families of children with challenging behavior.…”
Section: Resultsmentioning
confidence: 99%
“…These types of interventions were usually adapted from existing EBIs (71%). eHealth strategies applied include web-based parenting modules (included 4 to 12 interactive or structured parenting sessions), with (44, 45, 5253, 54, 56, 57) or without (42, 47, 48, 50, 55) additional e-communication or e-support for parents (e.g., phone coaching, e-reminders, feedback messaging, email, social media groups). There were also some studies focused on parent support interventions (including information and emotion support) and wellness promotion (purpose) for families of children with challenging behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 16 publications selected for the in‐depth analysis were systematic reviews ( n = 7), mHealth narrative reviews ( n = 2), mHealth interstage intervention feasibility studies ( n = 4), mHealth interstage randomized crossover study ( n = 1), mHealth engagement intervention ( n = 1), and a single mHealth adherence randomized controlled trial. The primary focus of each publication was mHealth in the interstage period for five (Bingler et al, 2018; Black et al, 2014; Cross et al, 2012; Harahsheh et al, 2016; Shirali et al, 2016), pediatrics and mHealth for four (Breitenstein, Brager, Ocampo, & Fogg, 2017; Canter, Christofferson, Scialla, & Kazak, 2019; Niksch, 2015; Taki, Campbell, Russell, Appleton, & Denney‐Wilson, 2019), and the remainder were general mHealth (Alexander & Staggers, 2009; Hamine, Gerth‐Guyette, Faulx, & Green, 2015; Kumar et al, 2013; Marcolino et al, 2018; Shaw et al, 2016; Simblett et al, 2018; Subhi, Bube, Rolskov Bojsen, Skou Thomsen, & Konge, 2015). All intervention studies are outlined in Table 1 and were single site with only one completed outside of the United States, in the United Kingdom (Taki et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…reported results from a randomized controlled trial of the ezPARENT program, an mHealth intervention for socioeconomically disadvantaged parents of young children to increase parent training to deter maltreatment and abuse. The engagement was a central element of the study's success, with usage rates showing 82% completion of education modules and parents logging in on 77% of days in the 3-month study period(Breitenstein et al, 2017). Although this group of infants were high risk in potentially different ways compared with infants with single ventricle congenital heart disease, the focus on engagement and a similar monitoring period of 3 months provide opportunities to extrapolate to the concept of parental mHealth adherence.Simblett et al (2018) reported a model of engagement based on their systematic review of mHealth remote monitoring where barriers and facilitators to engagement included changes in health status (hospitalization days where home monitoring is not needed), usability (technical malfunctions or broken devices), convenience (forgetting to use mHealth or weak cellular coverage), perceived utility (financial costs and poor data reliability of home monitoring), and internal parental or external motivation from the healthcare team.…”
mentioning
confidence: 99%
“…There are also examples of mHealth parenting and parenttraining interventions (Breitenstein et al, 2017), which similarly intervenes directly through a technological platform, to change behavior. Among these parent interventions relevant to violence prevention are those which seek to address adult mental health problems.…”
Section: Delivery Of Intervention Programsmentioning
confidence: 99%